Pemberdayaan Ekonomi Masyarakat Melalui Kerajinan Batik Tulis Giriloyo Wukisari Bantul Daerah Istimewa Yogyakarta - Iwin Arnova; Siti Nuraini; Widia Nurul Fadillah; Rinda Zelni Saputri; Anjelita Anjas Fadila; Yopi Aprizal (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Economic empowerment Increase the cost of living of the surrounding community, Increase economic contribution to the community, Increase foreign exchange, Become an inspiring model in empowerment throughout Indonesia. One of them is Batik Giriloyo, this study examines the Role of Giriloyo Wukisari Hand-Written Batik Crafts in supporting the economic resilience of the community in Wukisari Bantul, Special Region of Yogyakarta. This study discusses the role of Giriloyo hand-drawn batik crafts in improving the economic welfare of the local community. Thus, this study Increases Understanding of Economic Empowerment and provides insight into how the traditional craft industry can contribute to community welfare. This study uses a descriptive qualitative approach method with the aim of deeply understanding the process of community economic empowerment through hand-drawn batik crafts in Giriloyo, Special Region of Yogyakarta. Overall, the results of the study show that community economic empowerment through Giriloyo hand-drawn batik has a significant positive impact on various aspects of life. In terms of economy, this initiative has succeeded in increasing income and creating financial stability for craftsmen, opening up new business opportunities, and increasing people's purchasing power. In terms of social aspects, this empowerment increases the role of women in the family economy, strengthens the craftsman community through collaboration, and strengthens social relations. From a cultural perspective, this effort plays an important role in preserving the cultural heritage of Giriloyo batik tulis through the regeneration of skills in the younger generation. Although advances in technology and digital marketing open up wider market opportunities, the challenges of digital literacy still need to be overcome. Barriers such as limited capital, competition, and lack of access to global markets underscore the need for continued support from the government and the private sector to ensure the sustainability and development of community economic empowerment through Giriloyo batik tulis.